PENGGUNAAN FRASA ENDOSENTRIK APOSITIF DALAM KARANGAN WACANA BERITA - Sri Rahayu (AIJER: Algazali International Journal Of Educational Research, 2019)
Abstract: The Use of Appositive Endocentric Phrases in News Discourse Essays. This study aimed to describe the forms of the use of apositive endocentric phrases in news essay discourse at SMP Negeri 3 Mare Class VIII.B. This research used descriptive qualitative analysis techniques. This technique led to research that was used based on existing facts by describing and analyzing data qualitatively. Data from this study were obtained from news essay discourse in SMP Negeri 3 Mare Class VIII.B. The data that had been collected was given a code and text serial number along with paragraph number sequence. The object in this study was a student worksheet in the form of student essays. The data collection technique in this researchwas the documentation technique. The data collection phase includes: collecting student essays, reading one at a time and underlining the apositive endocentric phrases found in the news discourse. The data analysis phase includes: discussing one by one analyzing the data that has been studied, and drawing conclusions. The results of this study indicated that the form of apositive endocentric phrases that were used in news essays on students of SMP Negeri 3 Mare class VIII.B were subject positions in the form of nouns in the name category, there were also prepositional phrases marked with prepositions as clues such as 'in' , 'to', 'from' and 'to'.